2022
DOI: 10.3390/jcm12010278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Dermoscopic, Ultrasonographic, and Histopathologic Correlations in Kaposi’s Sarcoma Lesions and Their Differential Diagnoses: A Single-Center Prospective Study

Abstract: (1) Background: Kaposi’s sarcoma (KS) is an angioproliferative neoplasm typically appearing as angiomatous patches, plaques, and/or nodules on the skin. Dermoscopy and ultrasonography have been suggested as an aid in the diagnosis of KS, but there is little evidence in the literature, especially regarding its possible differential diagnoses. Our aim is to describe and compare the clinical, dermoscopic, and ultrasonographic features of KS and KS-like lesions. (2) Methods: we conducted a prospective study on 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…7 Kaposi sarcoma has also been reported in patients taking long-term daily systemic corticosteroids to treat rheumatoid arthritis, polymyalgia rheumatica, myasthenia gravis, nephrotic syndrome, and bullous pemphigoid. 6,8,9 Although Kaposi sarcoma is often suspected based on characteristic skin lesions, the diagnosis should be confirmed by histological examination of a skin biopsy. 1 Typical findings on hematoxylineosin staining include spindle cells and dermis vascular proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Kaposi sarcoma has also been reported in patients taking long-term daily systemic corticosteroids to treat rheumatoid arthritis, polymyalgia rheumatica, myasthenia gravis, nephrotic syndrome, and bullous pemphigoid. 6,8,9 Although Kaposi sarcoma is often suspected based on characteristic skin lesions, the diagnosis should be confirmed by histological examination of a skin biopsy. 1 Typical findings on hematoxylineosin staining include spindle cells and dermis vascular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A study of US patients who received solid organ transplants from 1987 to 2014 and had no history of Kaposi sarcoma or HIV infection found that 163 of 244 964 (0.07%) developed Kaposi sarcoma . Kaposi sarcoma has also been reported in patients taking long-term daily systemic corticosteroids to treat rheumatoid arthritis, polymyalgia rheumatica, myasthenia gravis, nephrotic syndrome, and bullous pemphigoid …”
Section: Discussionmentioning
confidence: 99%